Consumer Behavior Regarding Durable Goods - Azhagaiah, Ramachandran; Ezhilarasi, Eganathan (Indian Journal of Marketing, 2012)
The paper reveals the results of survey data analyzed on Mixer Grinders (MGs) (based on responses from 171 MG users in Puducherry). Kruskal Wallis (KW) H test, one-way ANOVA (F-test), and Conjoint Analysis (CA) are the statistical tools used for analyzing the data. The study shows that 45.7% of the respondents who have studied up to a degree use the branded MGs. The brand-wise analysis reveals that most of the housewives use Preethi Brand of MG, as compared to that of the other brands, which reveals that there is no significant relation between the brand preference of MGs and the occupational status of consumers. The brand ’Philips’ has been preferred for its "quality", while Crompton Greaves (CGs) has been preferred for its after-sales service. When comparing the MG brands, the cost of spare parts is moderate for all. Quality has been given first preference when comparing the perception of consumers towards MGs age-wise, while analysis with gender as the factor depicts that most of them prefer an "ISO" certified product. Educational status and occupation do not influence the brand preference as most of the respondents prefer "ISO" products, irrespective of their educational qualification and occupation. Perception by age with various features of MG shows that its features are given more importance. In respect of the consumers’ level of satisfaction, when compared with various features of MG, the educational status plays a significant role in giving preference to the "grinding capacity" of the MGs, while occupational status gives preference to "speed" of the MGs.